Triple selectin knockout (ELP-/-) mice fail to develop OVA-induced acute asthma phenotype - Banerjee Ena (BMC, 2011)
Abstract Objective The recruitment of leukocytes from circulation to sites of inflammation requires several families of adhesion molecules among which are selectins expressed on a variety of cells. In addition, they have also been shown to play key roles in the activation of cells in inflammation. Methods To explore the collective role of E-, L-, and P- selectins in OVA-induced Th2 mediated response in acute asthma pathophysiology, ELP-/- mice were used and compared with age-matched wildtype (WT). Results Asthma phenotype was assessed by measuring pulmonary function, inflammation and OVA-specific serum IgE, which were completely abrogated in ELP-/- mice. Adoptive transfer of sensitized L selectin+CD4+ T cells into naïve ELP-/- mice which post-OVA challenge, developed asthma, suggesting that L-selectin may be critically involved in the onset of Th2 response in asthma. Tissue resident ELP-deficient cells were otherwise functionally competent as proved by normal proliferative response. Conclusions: Comparative studies between ELP-/- and WT mice uncovered functional roles of these three integrins in inflammatory response in allergic asthma. All three selectins seem to impede inflammatory migration while only L-selectin also possibly regulates activation of specific T cell subsets in lung and airways.